EMLA Cream Effectively Reduces the Pain of Spinal Needle Insertion. Issue 6 (November 1996) - Sharma, Shiv K.; Gajraj, Noor M.; Sidawi, Elaine J.; Lowe, Kevin
Abstract : Background and Objective: EMLA cream is an effective topical anesthetic, which is commonly used for analgesia during venous cannulation in the pediatric population. This study was designed to compare the efficacy of EMLA cream with that of infiltration with lidocaine in relieving the pain associated with administration of spinal anesthesia. Methods: The patient population consisted of 41 ASA status I and II women scheduled for postpartum tubal ligation. Spinal anesthesia was administered with a 25-gauge spinal needle via a 20-gauge introducer. The patients were randomly allocated to receive either EMLA cream for a minimum of 30 minutes or infiltration with 3 mL of 1% lidocaine prior to spinal needle insertion. Pain during spinal needle insertion was assessed immediately after each procedure by a 10-cm visual analog scale. Results: Pain scores were significantly lower in the EMLA group (mean, 1.5) than in the lidocaine group (mean, 3.52) ( P < .001). The number of patients satisfied with the method of analgesia was significantly higher in the EMLA than in the lidocaine group (90% vs 55%, P < .05). Conclusion: EMLA cream is an effective alternative to lidocaine infiltration for analgesia during the administration of spinal anesthesia when using a 25-gauge spinal needle via a 20-gauge introducer. Application of EMLA cream for at least 30 minutes prior to spinal needle insertion is adequate to provide good anlagesia during needle insertion.